Increase in the glutamate transporter 1 and time withdrawal latency following wet cupping therapy in chronic constriction injury in rats - Hanik Badriyah Hidayati, - (Faculty of Anaesthesia, Pain and Intensive Care, AFMS, 2021)
Objective: Neuropathic pain (NP) is a chronic debilitating pain and is caused by disease or lesion of somatosensory system. NP respond worse to the pharmacological drugs leading to this pain still a big problem in medical treatment and furthermore make many patients seek alternative treatment. Wet cupping therapy (WCT) has been widely used to relief both of acute and chronic pain, but the mechanism for reducing pain has not yet been clear. Recent studies have shown that NP is associated with alteration of GLT-1/EAAT2, and WCT has beneficial role to reduce the pain in various pain models. This is the pilot study, no other study has applied WCT in chronic constriction injury (CCI) models, the most commonly employed animal model of NP. Therefore, we investigate the association between WCT and the reducing pain by looking at the increase of GLT-1 and time withdrawal latency (TWL) in rats with CCI. Methodology: The study design was randomized, post-test only, controlled trial with a total of 21 male rats (Rattus Norvegicus) with CCI, aged 4 months, weighing 220 to 250 g, randomly divided into three groups, P1 (sham CCI group), P2 (CCI group), and P3 (CCI group plus WCT). WCT had been applied 2 times/week for 3 weeks to all of the groups in paralumbar region, both left and right side. TWL was recorded to assess pain threshold of the rats by hot plate and the expression of GLT-1 on glial cells in spinal cord were counted. Results: This study revealed that mean ± SD values for P1, P2, and P3 were 7.20 ± 1.30, 2.57 ± 1.27, and 18.20 ± 3.50 respectively. There were significant differences in the TWL between groups P1-P2, P1-P3, and P2-P3 (p = 0.003, p = 0.0001, and p = 0.0001 respectively) and GLT-1 increase was significant between groups P2-P3 (p = 0.009). Conclusion: It can be concluded that wet cupping therapy decreases the pain by increasing the time withdrawal latency and GLT-1 in chronic constriction injury models. We suggest that wet cupping therapy as a promising method to reduce pain in peripheral neuropathic pain models. However, further investigation is still needed to confirm its mechanism of action.